Fish Fingerprints Signatures of Oil Contamination - Spilsbury, Francis David (Curtin University, 2022)
A laboratory exposure trial investigating the effects of crude oil and heavy fuel oil on Lates calcarifer (barramundi, or Asian seabass), including analysis of biochemical biomarkers, gut microbiome studies, otolith microchemistry and geochemical biomarkers. This work has developed a novel, non-subjective method for the forensic identification of source oil in the event of a spill, using multivariate analysis of the ecotoxicological effects exhibited by fish exposed to petroleum hydrocarbons.